Temperature Controls on the Erosion of Badland Slopes in the Nanxiong Basin, China - Chen, Zhi; Yan, Luobin; Peng, Hua; Shi, Hong (Frontiers in Earth Science, 2021)
Understanding the relationships between environmental variables and erosion rates in badlands is vital for forecasting sediment yields. While the controlling role of rainfall on badland erosion rates has long been recognized, here we assess the relative influences of temperature and precipitation on slope erosion rates in the Nanxiong Basin, Southeast China. The volume of weathered and transported fragments was measured within a bounded plot at ten-day intervals between May 1, 2016, and April 30, 2017, and temperature and precipitation were continuously recorded. Mann-Kendall τ correlation, Granger causality, impulse response, and variance decomposition analyses were performed. The results show that Granger causality relationships exist between the ten-day mean temperature (TMT) and ten-day mean erosion rates (TER) and between the ten-day total precipitation (TTP) amount and the TER. Moreover, our findings indicate that TMT and TTP explained 14.6 and 12.61% of the variability in slope erosion rates, respectively, which indicates that temperature had at least the same influence on slope erosion than precipitation. In addition, because 22.5% of the measured erosion occurred during periods when there were no erosive rain events, the importance of small dry slides for removing rock fragments from these humid slopes is emphasized.